Classroom activities to improve the students’ pragmatic ability to make appropriate complaint in English. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2021)
Making complaint is sometimes accepted as face threatening act if the speaker is unaware of strategies and language use and makes a complaint based on their own cultural norms in the target culture. So the activities given serve to facilitate the students with enough experience that can be implemented while making complaints.